Potential role of the Eph/ephrin system in colorectal cancer: emerging druggable molecular targets - João Figueira Scarini; João Figueira Scarini; Moisés Willian Aparecido Gonçalves; Moisés Willian Aparecido Gonçalves; Reydson Alcides de Lima-Souza; Reydson Alcides de Lima-Souza; Luccas Lavareze; Luccas Lavareze; Talita de Carvalho Kimura; Talita de Carvalho Kimura; Ching-Chu Yang; Albina Altemani; et al. (Frontiers in Oncology, 2024)
The Eph/ephrin system regulates many developmental processes and adult tissue homeostasis. In colorectal cancer (CRC), it is involved in different processes including tumorigenesis, tumor angiogenesis, metastasis development, and cancer stem cell regeneration. However, conflicting data regarding Eph receptors in CRC, especially in its putative role as an oncogene or a suppressor gene, make the precise role of Eph-ephrin interaction confusing in CRC development. In this review, we provide an overview of the literature and highlight evidence that collaborates with these ambiguous roles of the Eph/ephrin system in CRC, as well as the molecular findings that represent promising therapeutic targets.